PRODUKSI HIJAUAN MAKANAN TERNAK DAN KOMPOSISI BOTANI PADANG PENGGEMBALAAN ALAM PADA MUSIM HUJAN DI KECAMATAN AMARASI BARAT KABUPATEN KUPANG - Yulius Uli Hawolambani; Herayanti Panca Nastiti; Yoakim Harsuto Manggol (Universitas Nusa Cendana, 2015)
This research has been conducted in the area of pasture Subdistrict Amarasi Barat District Kupang. The aim of this research was to know production of fodder and forage botanical composition of field natural Grazing during the rainy season in the Amarasi West District, Kupang regency. The method used in this research was the measuremend and observation method. Measurement of forage production was done by using the